2020
DOI: 10.1016/j.stemcr.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Requirement of Euchromatic Histone Methyltransferase Activity during Reprogramming to Pluripotency

Abstract: Summary Methylation of histone 3 at lysine 9 (H3K9) constitutes a roadblock for cellular reprogramming. Interference with methyltransferases or activation of demethylases by the cofactor ascorbic acid (AA) facilitates the derivation of induced pluripotent stem cells (iPSCs), but possible interactions between specific methyltransferases and AA treatment remain insufficiently explored. We show that chemical inhibition of the methyltransferases EHMT1 and EHMT2 counteracts iPSC formation in an enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…A recent study showed that overexpression of the RAS oncogene in wild type mouse embryonic fibroblasts (MEFs) enhanced their dedifferentiation, but transformation of the same cells by deleting p53 or Arf tumor suppressors precluded it ( Ferreirós et al, 2019 ). Similar interactions and context dependency were observed for histone marks as well ( Nagaraja et al, 2019 ; Vidal et al, 2020 ). These data indicate that cancer cells diverge into distinct epigenetic programs, and likely change their cellular context, at the early stages of transformation.…”
Section: Pervasive Uncertainty In Targeting Cellular Componentssupporting
confidence: 75%
“…A recent study showed that overexpression of the RAS oncogene in wild type mouse embryonic fibroblasts (MEFs) enhanced their dedifferentiation, but transformation of the same cells by deleting p53 or Arf tumor suppressors precluded it ( Ferreirós et al, 2019 ). Similar interactions and context dependency were observed for histone marks as well ( Nagaraja et al, 2019 ; Vidal et al, 2020 ). These data indicate that cancer cells diverge into distinct epigenetic programs, and likely change their cellular context, at the early stages of transformation.…”
Section: Pervasive Uncertainty In Targeting Cellular Componentssupporting
confidence: 75%
“…Frontiers in Cell and Developmental Biology frontiersin.org reprogramming efficiency (Wang et al, 2011;Vidal et al, 2020). Onder et al showed that H3K79 dimethylation (H3K79me2) prevented repression of lineage-specific programs and acted as a barrier during reprogramming.…”
Section: Histone Changes During Reprogrammingmentioning
confidence: 99%
“…As an epigenetic mark that is mainly associated with gene repression, H3K9 methylation acts as a major obstacle to reprogramming. Induction of certain histone demethylases or using siRNAs against H3K9 methyltransferases has been found to enhance reprogramming efficiency ( Wang et al, 2011 ; Vidal et al, 2020 ). Onder et al showed that H3K79 dimethylation (H3K79me2) prevented repression of lineage-specific programs and acted as a barrier during reprogramming.…”
Section: Reprogramming and The Associated Epigenetic Changesmentioning
confidence: 99%
“…While these antibodies were chosen for their widespread use in many publications [39][40][41][42][43], we considered that the antibodies themselves may lack specificity; however, we found that the antibodies were indeed specific when histone peptides were displayed in a different context. Specifically, when the same set of peptides was linked to the surface of yeast (instead of magnetic beads) through the display of modified monovalent streptavidin (mSA) [44][45][46] (Figure 3c), the same antibodies were able to specifically bind to their target epitope and showed significantly less binding to nontarget epitopes (Figure 3b, right).…”
Section: Antibodies Label More Specifically When Histone Peptides Are Presented On Yeast Versus Bead Surfacesmentioning
confidence: 99%